LANGUAGE SOCIALIZATION AND GENRE ADHERENCE IN REDDIT.COM - Titak, Ashley (AoIR Selected Papers of Internet Research, 2015)
Social networking sites (SNSs) are receiving attention from researchers from various theoretical linguistic frameworks. However, there is a paucity research considering language use in digital genres from a language socialization perspective. This study examines Reddit, a popular forum community, with a language socialization perspective, using a comparative corpus analysis to analyze language patterns. A comparative corpus analysis involves comparing the subcorpus in question (e.g., First Year Users) to a larger reference corpus using frequent word, keyword, and n-gram analysis to note the difference in language patterns between comments. Given my interest in socialization, I compare language in posts according to the user's year of use (e.g., First Year users, Second Year users, etc.), the comment's score assigned by other community members (e.g., positive and negative), and the sub-communities (e.g., subreddits such as the Best of Netflix subreddit) in which the posts were made, in an effort to explore how language may vary according to these variables and to identify potential trends.